In Vitro Assessment of Shiitake Mushroom (Lentinula edodes) Extract for Its Antigingivitis Activity. (28th September 2011) - Ciric, Lena; Tymon, Anna; Zaura, Egija; Lingström, Peter; Stauder, Monica; Papetti, Adele; Signoretto, Caterina; Pratten, Jonathan; Wilson, Michael; Spratt, David
Abstract : Gingivitis is a preventable disease characterised by inflammation of the gums due to the buildup of a microbial biofilm at the gingival margin. It is implicated as a precursor to periodontitis, a much more serious problem which includes associated bone loss. Unfortunately, due to poor oral hygiene among the general population, gingivitis is prevalent and results in high treatment costs. Consequently, the option of treating gingivitis using functional foods, which promote oral health, is an attractive one. Medicinal mushrooms, including shiitake, have long been known for their immune system boosting as well as antimicrobial effects; however, they have not been employed in the treatment of oral disease. In the current study, the effectiveness of shiitake mushroom extract was compared to that of the active component in the leading gingivitis mouthwash, containing chlorhexidine, in an artificial mouth model (constant depth film fermenter). The total bacterial numbers as well as numbers of eight key taxa in the oral community were investigated over time using multiplex qPCR. The results indicated that shiitake mushroom extract lowered the numbers of some pathogenic taxa without affecting the taxa associated with health, unlike chlorhexidine which has a limited effect on all taxa.